2016
DOI: 10.1016/j.tem.2016.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Sphingolipid De Novo Biosynthesis: A Rheostat of Cardiovascular Homeostasis

Abstract: Sphingolipids are both, fundamental structural components of the eukaryotic membranes and signaling molecules regulating a variety of biological functions. Highly bioactive lipids, ceramide and sphingosine-1-phosphate have emerged as important regulators of cardiovascular functions in health and disease. In this review we discuss recent insights into the role of sphingolipids, particularly ceramide and sphingosine-1-phosphate, in the pathophysiology of the cardiovascular system. We also highlight advances into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 112 publications
(141 reference statements)
1
48
0
Order By: Relevance
“…Besides traditional risk factors, changes in sphingolipids may contribute to the pathogenesis of cardiovascular disease 1,43 . Higher plasma levels of sphingomyelin are also associated with increased atherosclerosis and they have been proposed as independent risk factors for coronary heart disease in humans 44 .…”
Section: Cardiovascular Diseasesmentioning
confidence: 99%
“…Besides traditional risk factors, changes in sphingolipids may contribute to the pathogenesis of cardiovascular disease 1,43 . Higher plasma levels of sphingomyelin are also associated with increased atherosclerosis and they have been proposed as independent risk factors for coronary heart disease in humans 44 .…”
Section: Cardiovascular Diseasesmentioning
confidence: 99%
“…Literature on ceramide biology also links these molecules with many atherosclerotic processes, such as lipoprotein aggregation, uptake of lipoproteins and accumulation of cholesterol within macrophages, regulation of nitric oxide synthesis, production of reactive oxygen species, platelet activation, and expression of various cytokines. Moreover, experimental studies in animals have also shown that ceramides are associated with the development of atherosclerosis [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…1A-G). There are 3 major pathways for sphingolipid biosynthesis [8] as shown in figure 1H: (1) the sphingomyelinase pathway, which uses sphingomyelinase to break down sphingomyelin in the cell membrane and release ceramide; (2) the de novo pathway, which synthesizes ceramide from palmitate and serine; and (3) the salvage pathway, which can generate ceramide through breakdown of complex sphingolipids that are ultimately converted into sphingosine, which then undergoes reacylation to form ceramide. Therefore, we next looked if the expressions of the key genes ( Fig.…”
Section: Resultsmentioning
confidence: 99%